69.2k views
1 vote
6t -20-32u6t−20−32u6, t, minus, 20, minus, 32, u when t=6t=6t, equals, 6 and u=\dfrac14u=

4
1
​ u, equals, start fraction, 1, divided by, 4, end fraction.

User LC Yoong
by
6.0k points

2 Answers

0 votes

Answer:

8

Explanation:

Let's substitute t = 6 and u = 1/4 into the expression.

6t - 20 - 32u

= 6(6) - 20 - 32(1/4)

= 36 - 20 - 8

= 8

Hope you understood! <3

User Ayesha
by
6.1k points
1 vote

The question is:

Evaluate 6t−20−32u when t=6 and u=1/4

Answer:

8

Explanation:

The given expression is:


6t-20-32u

We need to evaluate the expression for the given values of t and u. Substituting t=6 and u=1/4 in the above expression we get:


6(6)-20-32((1)/(4) )\\\\ =36-20-8\\\\ =8

Thus, the give expression is equal to 8 for t=6 and u=1/4

User Adriennetacke
by
5.9k points